The power of parenting: mitigating conduct problems among adolescents carrying genetic risk - Choi, Maia; Dash, Genevieve F.; Kuo, Sally I.; Aliev, Fazil; Poore, Holly E.; Brislin, Sarah J.; Dick, Danielle M. (Frontiers in Child and Adolescent Psychiatry, 2025)
Conduct problems (CPs), including aggression, antisocial behavior, and rule-breaking, emerge in childhood and adolescence. Evidence from twin studies shows that CPs are heritable, with approximately 50% of the variance accounted for by genetic influences. Parenting is one prominent and, importantly, modifiable environmental factor in the development of CPs. This study tested whether parental monitoring moderated the associations between genetic liability and CPs in adolescents aged 12–14. We found parental monitoring significantly moderated the association between genetic risk for externalizing and CPs in adolescence. These findings underscore the utility of family-based prevention and intervention efforts, particularly for children at elevated genetic risk.